Glucose and Lipid Metabolism, Bone Density, and Body Composition in Individuals with Williams Syndrome - Shaikh, Sofia (Clin Endocrinol (Oxf), 2018)
OBJECTIVE: We assessed body composition, bone mineral density (BMD), glucose, and lipids in Williams syndrome (WS), a rare microdeletion disorder. DESIGN: Individuals with WS had outpatient assessment at Massachusetts General Hospital. Controls were selected from the National Health and Nutrition Examination Survey (NHANES 2005–2006). PATIENTS: 22 individuals with WS, each matched by age, sex, and race to 4 NHANES controls MEASUREMENTS: Blood sampling, oral glucose tolerance test, dual energy x-ray absorptiometry (DXA) scan RESULTS: WS and control groups were 59% female and 29 ± 8 years old. Compared to controls, individuals with WS were shorter but had similar body weight, with more fat and less lean mass. Percent body fat was higher in WS even after adjusting for BMI (+2.1% [95% CI 0.4, 3.9%]). Four WS patients had abnormal lower extremity fat accumulation resembling lipedema. HbA1c (+0.5% [0.2, 0.7]) and 2-hour glucose (+68mg/dL [44, 93]) were higher in WS versus controls, differences which persisted after adjusting for BMI. Fasting glucose was comparable between groups. LDL (−18mg/dL [−35, −2]) and triglycerides (−45mg/dL [−87, −2]) were significantly lower in WS. Whole body BMD was significantly lower (−0.15g/cm(2) [−0.20, −0.11]) in WS, and this remained true controlling for height (−0.06 g/cm(2) [−0.11, −0.02]). Vitamin D was <30ng/mL in 81% of those with WS. CONCLUSIONS: On average, adults with WS have increased fat, decreased lean mass, impaired glucose homeostasis, and reduced BMD. Clinical efforts to build muscle and bone mass, and to ensure vitamin D sufficiency, are warranted. Genotype-phenotype research efforts are also warranted.